The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1997
DOI: 10.3109/01674829709080701
|View full text |Cite
|
Sign up to set email alerts
|

Labor pain is reduced by massage therapy

Abstract: Twenty-eight women were recruited from prenatal classes and randomly assigned to receive massage in addition to coaching in breathing from their partners during labor, or to receive coaching in breathing alone (a technique learned during prenatal classes). The massaged mothers reported a decrease in depressed mood, anxiety and pain, and showed less agitated activity and anxiety and more positive affect following the first massage during labor. In addition, the massaged mothers had significantly shorter labors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
8

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 14 publications
0
58
0
8
Order By: Relevance
“…Most previous studies found that massage therapy techniques were effective in LP alleviation (49)(50)(51)(52)(53)(54)(55)(56)(57)(58). A study showed that although massage therapy could alleviate LP during the first and second stages of labor, it had no significant effects on LP in the third stage of labor (58).…”
Section: Massage Therapymentioning
confidence: 99%
“…Most previous studies found that massage therapy techniques were effective in LP alleviation (49)(50)(51)(52)(53)(54)(55)(56)(57)(58). A study showed that although massage therapy could alleviate LP during the first and second stages of labor, it had no significant effects on LP in the third stage of labor (58).…”
Section: Massage Therapymentioning
confidence: 99%
“…Yapılan randomize kontrollü bir çalışmada doğum sırasında beş saat boyunca, kadınlara her yirmi dakikada bir eşleri tarafından ayak, sırt, el ve baş masajının kadınların ağrısını ve anksiyetesini azaltıp duygusal durumunu daha da iyileştirdiği saptanmıştır [38]. Masajın doğum ağrısına olan etkisinin incelendiği randomize kontrollü başka bir çalışmada, doğumun tüm fazlarında masaj uygulanan deney grubunun lehine ağrı puanlarının kontrol grubuna oranla anlamlı derecede düşük bulunmuştur [39]. Yine başka bir randomize çalışmada, partnerleri tarafından masaj uygulanan ve nefes alma tekniklerini kullanan deney grubunun ağrı puanlarının, yalnızca nefes alma tekniklerinin kullanıldığı kontrol grubuna oranla anlamlı derecede düşük olduğu saptanmıştır [40].…”
Section: Doğumda Terapötik Dokunmaunclassified
“…Avaliações clínicas bem conduzidas têm atestado a eficácia da massagem e da quiropraxia no tratamento da dor da coluna. Na obstetrícia, a massagem pode ser praticada pela parteira, enfermeira ou pelo marido, pois seu efei-to reconfortante na parturiente reduz o consumo de analgé-sico durante o trabalho de parto [44][45][46] . A quiropraxia é a massagem mais efetiva no controle de dor nas costas, estatisticamente a queixa mais comum entre os trabalhadores que não se preocupam com os princípios ergonômicos básicos no seu dia-a-dia.…”
Section: Toque De Mãounclassified
“…Esta massagem antiálgica alternativa não exclui a terapêutica clínico-cirúrgica clássica, pois sua eficácia ainda não está plenamente estabelecida em ensaios clínicos mais rigorosos. Sua prática é aceita nos sistemas de saúde com base numa dupla crença: que o sistema nervoso é o mais importante determinante da saúde; que muitas algias lombares, dorsais, cervicais e da cabeça são causadas por subluxação espinal que responde de modo favorável à manipulação adequada [43][44][45][46][47][48][49][50][51][52][53][54][55][56] .…”
Section: Toque De Mãounclassified
See 1 more Smart Citation